Case matching and syncretism in ATB‐dependencies. (14th October 2019) - Hein, Johannes; Murphy, Andrew
Abstract: Syncretism has been reported to have the peculiar property of repairing violations of syntactic constraints, e.g. with agreement (Schütze 2003, Bhatt & Walkow 2013) and case matching (Citko 2005, van Craenenbroeck 2012). This paper puts forward the view that in one well‐reported instance of syncretism repair of case‐matching violations with ATB‐movement, this repair follows directly from the nature of ATB movement. We pursue a novel movement‐based analysis in which ATB movement involves the actual fusion of two syntactic objects, via intersection of feature sets. As well as deriving the one‐to‐many relation between fillers and gaps in ATB, we show how the 'repair' effect of syncretism with case matching violations follows naturally under this approach.